2017
DOI: 10.3201/eid2305.161100
|View full text |Cite
|
Sign up to set email alerts
|

ESBL- and Carbapenemase-Producing Enterobacteriaceae in Patients with Bacteremia, Yangon, Myanmar, 2014

Abstract: Among 42 gram-negative bloodstream isolates from inpatients in 3 hospitals in Yangon, Myanmar, admitted during July–December 2014, 16 (38%) were extended-spectrum β-lactamase–producing Enterobacteriaceae and 6 (14%) produced carbapenemase. The high prevalence of multidrug-resistant gram-negative bacteria raises concerns about the empiric treatment of patients with sepsis in Yangon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 8 publications
5
17
2
Order By: Relevance
“…Phenotypic testing of ESBL and carbapenemase production by the isolated E. coli showed that out of the 88 isolates; 49 patients (55.68%) were ESBL producers and 30 (34.09%) were carbapenemase producers. This finding is consistent with the high proportion of ESBL production reported in a study conducted in Egypt also, showing more than half (54.5%) of isolated E. coli positive for ESBL [20] and in New Zealand as about half of E. coli isolates produced ESBL [21]. Similar results in the USA [22] and India [23] have been reported as prevalence rates of ESBL were from 35.0 to 42% for E. coli.…”
Section: Discussionsupporting
confidence: 89%
“…Phenotypic testing of ESBL and carbapenemase production by the isolated E. coli showed that out of the 88 isolates; 49 patients (55.68%) were ESBL producers and 30 (34.09%) were carbapenemase producers. This finding is consistent with the high proportion of ESBL production reported in a study conducted in Egypt also, showing more than half (54.5%) of isolated E. coli positive for ESBL [20] and in New Zealand as about half of E. coli isolates produced ESBL [21]. Similar results in the USA [22] and India [23] have been reported as prevalence rates of ESBL were from 35.0 to 42% for E. coli.…”
Section: Discussionsupporting
confidence: 89%
“…In a survey conducted in a tertiary-care hospital and two private hospitals in Yangon, Myanmar, Escherichia coli and K. pneumoniae isolates carrying bla NDM genes were isolated (17). E. coli isolates carrying the bla NDM genes were also found in another hospital in Yangon (18), suggesting that organisms carrying these genes are spreading in the region.…”
mentioning
confidence: 99%
“…1. Antibiotic resistance is a burning issue in the field of medicine which complicate treatment of infected patients (19) . One of the mechanisms by which Gram-negative bacteria acquire resistance to beta-lactam antibiotics is through the production of betalactamases.…”
Section: Resultsmentioning
confidence: 99%